Urban Planning and Information and Communication Technology: Ideas and Facts - Galit Cohen; Marina van Geenhuizen; Peter Nijkamp (Tinbergen Institute, 2001)
In our modern network world, ICT acts as a connecting and integratingmechanism. Information (data, knowledge)has become a core constellation in an open economy. The avalanche ofinformation supply however, has not keptpace with the use of information by decision-making bodies.Especially in the public domain we observe often aninsurmountable gap. The actual use of opportunities offered by theICT sector to the public domain isdisappointingly low. The paper sets out to explain the existence ofimpediments in information acceptance and usein urban policy making. Particular attention will be given to theperception of the information potential by planners,experts and decision-makers. In this respect various constraintsexist in terms of lack of awareness of ICT policies,and lack of consensus about goals and means of ICT policies. Theanalysis will be illustrated by reference to aDutch study on the role of the advanced information sector in modernurban planning and administration.
Keywords: 330; ICT policies; local authorities; decision-makers; perceptions; Kommunalplanung; Kommunalpolitik; Informationstechnik; Telekommunikationspolitik; Niederlande